What hunts inside the shadows - Woods, Harper L. (Woods, Harper L. Of flesh & bone, 2025)
"Once, I fell in love with a man who deceived me. For weeks, he stood by my side, twisting his words into pretty half-truths. He enraptured me with his smooth temptation, leaving no corner of my being untouched. He consumed my mind and my body, then finally claimed my heart for himself. But Caelum's true identity is terrifying enough to bring me to my knees. Then, I discovered the truth of who he is. Caldris is whispered in the Nothrek wind. The legend we only speak of with hushed words, in shuttered rooms, for fear of drawing his wrath once again. His intentions are a mystery, his desires impure, and he seeks to shackle me to his side for all eternity. With the Wild Hunt as our guard, he points us back to where it all began: the village of Mistfell and the boundary where the Veil once shimmered in the wind. Now, another secret crouches, poised to change everything. The Mist Guard have been sworn to keep us from crossing into Alfheimr, and from treading Faerie soil, even if innocents must pay with their lives. They have orders to resurrect Mistfell's shimmering barrier, but, once again, there's a greater cost than what has been revealed. Once, the people of Northrek blamed me when the Veil fell. Soon, they'll want me to pay the price the magic requires." --